The importance of water management in hotels: a framework for sustainability through innovation - Kasim, Azilah; Gursoy, Dogan; Okumus, Fevzi; Wong, Anthony (Routledge, 2014)
This paper highlights the global phenomenon of the crisis in the quality and quantity of water supplies and how tourism generally and hotels specifically may have contributed to the situation.The major internal and external barriers for Small Medium Enterprises adopting Environmental Management Systems, including water, are listed. The paper proposes a water management framework for hotels and other types of accommodation that leverages on the concept of innovation.Taking into account the various levels of knowledge and technological capabilities in water management, the framework is developed based on the commonly known 3R approach in environmental management, with the addition of another R (Reaching).It is proposed that hotels can innovate and enhance their water management approaches under these 4Rs: Innovative Reducing,Innovative Reusing, Innovative Reaching and Innovative Recycling.The framework offers examples and strategies about how hotels of different sizes, with differing financial, technical, knowledge and managerial capacities could address the challenge of implementing water management and obtain commercial benefit.A detailed case study is provided of a gray and black water recycling system in a Malaysian resort. Other examples of a range of water management methods are also discussed.